Pengaruh Tehnik Pursed Lip Breathing terhadap Nilai Saturasi Oksigen Pasien Tuberkulosis Paru di RSUD Raja Ahmad Tabib Provinsi Kepulauan Riau - Sari, Meily Nirna; Rahardiantini, Ikha; Suheriani, Dwi (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2021)
Pulmonary tuberculosis is an infectious disease that is still a worldwide concern as the top infectious disease in the world. One of the interventions that can be done to reduce shortness of breath in pulmonary tuberculosis patients is the pursed lip breathing technique. The purpose of the study was to determine the effect of pursed lip breathing on the oxygen saturation value in pulmonary tuberculosis patients. The aim of the study was to determine the effect of pursed lip breathing on the saturation value. oxygen in pulmonary tuberculosis patients. The research method used a quasi-experimental design with one group pretest and posttest without control with a pre and post pursed lip breathing approach with a sample of 21 people, purposive sampling was used. The non-parametric hypothesis was tested by using the Wilcoxon test. The results of the bivariate test showed that there was an effect of pursed lip breathing on the increase in oxygen saturation in pulmonary tuberculosis patients with Value 0.005. Pursed lip breathing as an alternative for independent nurses to increase oxygen saturation in hospitalized pulmonary tuberculosis patients